Exploring the characteristics of adults' online learning activities: a case study of EdX online institute - Yuewei Shi; Xi Lin (Association for Learning Technology, 2021)
Online learning has become a prevailing trend among adult learners. Therefore, this study investigated the learning time preference and the relationship between the course completion and learning activities among adult learners based on data from one online learning platform. Results indicate that a periodical fluctuation of participating online course study exists among adult learners. Additionally, the activity of posting on the discussion board is a main learning activity factor that influences their online course completion. It is expected that this study would help online learning system designers, education administrators and instructors to better understand the characteristics of adult learners and their learning activities to provide better accessibility and flexibility in online learning environments for them.